Acute paediatric kidney replacement therapies in Europe: demographic results from the EurAKId Registry. Issue 4 (29th September 2021) - Guzzo, Isabella; de Galasso, Lara; Bayazit, Aysun Karabay; Yildizdas, Dincer; Schmitt, Claus Peter; Hayes, Wesley; Shroff, Rukshana; Jankauskiene, Augustina; Virsilas, Ernestas; Longo, Germana; Vidal, Enrico; Mir, Sevgi; et al.
ABSTRACT: Background: Acute kidney injury (AKI), particularly that requiring dialysis, is a severe complication in hospitalized children that is associated with high morbidity and mortality. A prospective European AKI registry (EurAKId registry, NCT02960867) was created to describe the epidemiology and outcomes of paediatric patients treated with acute dialysis. Methods: Children were recruited who were between 0 and 18 years of age and were treated both in and outside the paediatric intensive care unit (PICU) with peritoneal dialysis (PD), haemodialysis (HD) or continuous kidney replacement therapy (CKRT) for AKI or metabolic derangement, fluid overload (FO), sepsis or respiratory distress. Five age groups and 12 categories of primary diseases were defined. Results: Data on 340 patients were analysed, of whom 86% received dialysis for AKI and 14% for reasons other than AKI. Boys accounted for 60% of the patients. Illness severity was greater in children with cardiac and haematologic diseases than those with kidney diseases. Most patients received dialysis in the PICU (84%). The most frequently used dialysis modality was CKRT (64%), followed by PD (14%) and HD (14%). The overall survival rate was 65%. Survival was significantly lower in children with three comorbidities than in children with no comorbidities (41% and 83%; P < 0.001). Conclusions: The EurAKId registry is the first prospective registry considering paediatric acute kidney replacement therapies (KRTs) in both critical and non-critical care settings, focusing on the three dialysis modalities in Europe. The clinical indications for KRT have expanded; our population was characterized by critically ill patients, primarily boys, who frequently received dialysis in the PICU with CKRT.